ANALGESIC EFFICACY AND SPINAL MOBILITY IMPROVEMENT OF ELECTRO-LONG NEEDLE ACUPUNCTURE COMBINED WITH TAM TY THANG DECOCTION IN TREATING SCIATICA DUE TO WIND-COLD-DAMPNESS PATTERN (Vietnam Journal of Community Medicine, 2026)
Objectives: Evaluating the analgesic efficacy and mobility improvement of electro-long needle acupuncture combined with Tam ty thang decoction in patients with sciatica of the wind-cold-dampness pattern.Research methods: A controlled clinical trial comparing before and after treatment was conducted on 60 patients equally divided into a study group and a control group at Thai Binh Traditional Medicine Hospital from October 2024 to May 2025.Results: After 14 days of treatment, the study group’s average VAS score decreased to 1.17 ± 0.38 points, significantly lower than the control group (2.2 ± 0.48 points) with p < 0.05. The lumbar spine flexibility (Schober index) of the study group reached 4.38 ± 0.85 cm, higher than the control group (3.52 ± 0.76 cm, p < 0.05). Indicators for Lasègue sign amplitude and range of motion (flexion, extension, lateral bending) in the study group showed better improvement than the control group (p < 0.05). The rate of good treatment results in the study group reached 80%, higher than that of the control group (50%).Conclusion: The regimen of electro-long needle acupuncture combined with Tam ty thang decoction demonstrates superior efficacy in pain relief and functional recovery of lumbar spine mobility compared to routine electro-acupuncture after 14 days of treatment.
Keywords: Sciatica, electro-long needle acupuncture, Tam ty thang, traditional medicine, mobility improvement.